Analysis of triangular cross-section slender bodies in supersonic regime using RANS simulations - Bourny, Quentin; Proenca, Anderson R.; Di Pasquale, Davide; Prince, Simon A. (American Institute of Aeronautics and Astronautics (AIAA), 2023)
This paper presents an investigation on the ability of RANS simulations to capture the aerodynamic forces and the flow topology of triangular cross-section slender bodies. At Cranfield University’s Transonic and Supersonic Wind Tunnel, force measurements and Schlieren images were obtained at zero incidence, Mach number equals to 2.5, and Reynolds number of 2.38 · 10^5 (based on section width). Tests were performed for three bodies of different nose geometries, but constant nose fineness ratio of 1.732. Tests were compared with RANS simulations for three turbulence models: Spalart-Allmaras, k− epsilon Realizable and k − omega SST using the ANSYS Computational Fluid Dynamics software Fluent. In addition, simulations for a configuration presented in the literature which investigated several angles of attack were also conducted. At Mach 2.5, the normal force was predicted accurately by all turbulence models. The axial force, however, was clearly predicted more accurately with the k − epsilon Realizable model. At the other hand, this turbulence model showed inferior ability to capture the flow features, particularly the leeside vortices. Spalart-Allmaras and k − omega SST gave similar results.